Reclaiming Our Asian American/Pacific Islander Identity for Social Justice and Empowerment (Raise)| An Empowerment Circle for East Asian, South Asian, Southeast Asian, and Pacific Islander College-Aged Women - Shen, Courtney (Pepperdine University, 2017)
This dissertation outlines the literature and methods used to create the Women’s RAISE Circle, a culturally-specific intervention for Asian American/Pacific Islander (AAPI) women in a university or college setting. The term Asian American/Pacific Islander women is used to indicate inclusivity of women from all of the AAPI ethnic communities. The acronym RAISE represents the rationale and purpose of the circle: “ Reclaiming our Asian American/Pacific Islander Identity for Social justice and Empowerment.” Thus, the RAISE Circle provides a space for AAPI women to voice their concerns related to experiences of racism, sexism, and other forms of oppression. Included activities also seek to promote an exploration of personal and interpersonal experiences with intersecting identities and engagement in difficult conversations about oppression, power, and privilege. As an empowerment group, the RAISE Circle aims to help participants feel empowered to bring their concerns to the broader community and continue working for social justice for AAPI people. This dissertation includes the RAISE Circle Facilitator’s Handbook and Primer, indications for use, limitations, and implications for the future.